Implementasi Layanan Bimbingan Kelompok dengan Teknik Psikodrama dalam Mengatasi Perilaku Bullying di SMP - Afnisela Palloan; Jeane Marieske; Bittoen Bittoen; Selvi Datu Arruan; Yabes Rapang (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Bullying in junior high schools often results in serious psychological and social impacts, such as fear, low self-esteem, and decreased academic achievement. This study aims to examine the implementation of group guidance services using psychodrama techniques in addressing bullying behavior in junior high school students. The method used was a qualitative approach with a library research study, utilizing various existing sources such as scientific journals, books, and articles relevant to the topic of bullying and psychodrama. Data were collected through a literature search, selecting appropriate sources, and grouping them based on the study theme. Data analysis refers to the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the application of psychodrama techniques in group guidance can increase empathy, self-awareness, and social communication skills in students, resulting in significant changes in the intensity and frequency of bullying behavior. Thus, psychodrama techniques can be a relevant approach in group guidance services to address bullying behavior in junior high school students, as they can encourage deeper social understanding and emotional changes.